The Influence of Dietary Supplements on Exercise-Induced Gut Damage and Gastrointestinal Symptoms: A Systematic Review and Meta-Analysis - Robyn Aitkenhead (Nutrients, 2025)
Endurance exercise, especially under heat stress, temporarily compromises the integrity of the intestinal barrier in healthy individuals. Consequently, there is growing interest in developing effective dietary strategies to alleviate exercise-induced gastrointestinal symptoms and gut damage. This meta-analysis investigated the effects of dietary supplements on mitigating these challenges. The search was performed in November 2024 following PRISMA guidelines, and 26 peer-reviewed studies were included across three meta-analyses: (1) gastrointestinal symptoms, (2) circulating intestinal fatty acid-binding protein (i-FABP), and (3) exercise performance. The moderating effect of variables was assessed via sub-group analysis and meta-regression. Overall, there was no pooled effect of supplement interventions on gastrointestinal symptoms (Hedges’ g = 0.42, 95% CI −0.17: 1.02, p = 0.15), and probiotics had a moderate significant effect for gastrointestinal symptoms (Hedges’ g = −0.62, 95% CI −1.01; 1.01, p = 0.05). There was a significant increase in i-FABP concentrations pre- to post exercise (∆106%; Hedges’ g = 1.01, 95% CI 0.63; 1.38, p = 0.01). There were no pooled or sub-group differences for exercise performance for any supplements (p = 0.53). Moderate-to-large heterogeneity was observed across studies (I2 ≥ 58.6%), and candidate moderators (exercise duration, modality, and environmental temperature) had no significant effect on any outcomes (p > 0.05). A significant increase in circulating i-FABP during exercise was observed. However, when examining the effects of different supplement categories, although significance was observed for a select few supplements, the changes in i-FABP, gastrointestinal symptoms, and exercise performance were outside of clinical relevance. Although probiotics showed a moderate significant effect for gastrointestinal symptoms, the conflicting findings across studies may have been due to inadequate control of confounding variables across studies. Further research is required to assess the alternative dietary supplements’ effects on gastrointestinal health and exercise performance, particularly under varied environmental conditions, where more rigorous control for cofounding factors is implemented.